1997
DOI: 10.1002/(sici)1097-0142(19971225)81:6<337::aid-cncr7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The AutoPap 300 QC system multicenter clinical trials for use in quality control rescreening of cervical smears

Abstract: The AutoPap 300 QC System provides the potential for a marked increase in the number of false-negative cervical cytology cases that can be detected on QC rescreening. A significant reduction in laboratory false-negative rates can be expected if this device is utilized in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…This level of sensitiv-ity is comparable to clinical trial data which found a sensitivity for an endocervical component of 82.1%. 44 In the present study, the identification of an endocervical component on manual screening was determined solely on the presence of endocervical glandular cells. The decision not to include squamous metaplastic cells in the assessment of specimen adequacy was based on published findings which suggest that these cells are identified less reproducibly than endocervical columnar cells.…”
Section: Discussionmentioning
confidence: 99%
“…This level of sensitiv-ity is comparable to clinical trial data which found a sensitivity for an endocervical component of 82.1%. 44 In the present study, the identification of an endocervical component on manual screening was determined solely on the presence of endocervical glandular cells. The decision not to include squamous metaplastic cells in the assessment of specimen adequacy was based on published findings which suggest that these cells are identified less reproducibly than endocervical columnar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies aimed at assessing AutoPap system performance have focused on higher sensitivity and on reduced reading workload compared with conventional reading,1–5, 12 and few have addressed specifically the issue of the NPV of an NFR report 11. NPV for CIN2+ is assumed to be very high, but not absolute, and because some false negatives are expected, a routine quality control measure, such as manual review of a random subset of cases reported as NFR, can be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Automated reading of Papanicolaou (Pap) smears by the AutoPap (AutoPap Primary Screening System 300, Tripath Imaging Inc., Burlington, NC) system (presently commercialized as FocalPoint) has been proposed as a measure to reduce manual reading workload, and possibly overall costs, in current screening practice 1–5. AutoPap is reported to code as No Further Review (NFR) up to 25% of total smears, which may be safely assumed to be negative without conventional manual reading 3…”
mentioning
confidence: 99%
“…The FDA‐approved algorithm in‐use today ranks slides for severity, typically within batches of about 150 stained slides. The initial indication was to define women whose cytology indicated such low risk that cytotechnologist review was not needed . However, instead we developed a new algorithm that defines the most severely abnormal slides among HPV‐positive women.…”
Section: Methodsmentioning
confidence: 99%
“…FocalPoint performs a high‐speed, magnified scan, and outputs 160 binary or quantitative “features” of the cytology slide, such as presence of different cell types, nuclear size, chromatin density, and nuclear contour . The preset algorithm is designed for general screening, i.e ., review of batches of mainly negative slides from mainly HPV‐negative women.…”
Section: Methodsmentioning
confidence: 99%